2021
DOI: 10.1038/s41569-021-00559-8
|View full text |Cite
|
Sign up to set email alerts
|

Global epidemiology, health burden and effective interventions for elevated blood pressure and hypertension

Abstract: Global, regional and national levels National and multi-country studies. Supplementary Table 1 summarizes the studies that investigated blood pressure and hypertension trends in individual countries for a period of ≥20 years. The studies that compared multiple countries are summarized in Key points• Hypertension is more prevalent in low-income and middle-income countries than in high-income countries. • In 2015, 8.5 million deaths were associated with high blood pressure, 88% of which were in low-income and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
540
0
34

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 795 publications
(580 citation statements)
references
References 254 publications
6
540
0
34
Order By: Relevance
“…We used data from 1990 to 2019, collated by the NCD Risk Factor Collaboration (NCD-RisC), as detailed previously 6 and summarised in the appendix (pp 2-3). The inclusion criteria were that (1) data were collected using a probabilistic sampling method with a defined sampling frame; (2) data were from population samples at the national, sub-national (covering one or more subnational regions), or community (one or a small number of communities) level; (3) systolic blood pressure and diastolic blood pressure were measured; and (4) data on hypertension treatment were available.…”
Section: Data Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…We used data from 1990 to 2019, collated by the NCD Risk Factor Collaboration (NCD-RisC), as detailed previously 6 and summarised in the appendix (pp 2-3). The inclusion criteria were that (1) data were collected using a probabilistic sampling method with a defined sampling frame; (2) data were from population samples at the national, sub-national (covering one or more subnational regions), or community (one or a small number of communities) level; (3) systolic blood pressure and diastolic blood pressure were measured; and (4) data on hypertension treatment were available.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Studies were excluded if they (1) included or excluded participants on the basis of health status; (2) were done only among minority ethnic groups or specific educational, occupational, or other socioeconomic groups; (3) recruited participants through health facilities, except studies whose sampling frame was health insurance schemes in countries where at least 80% of the population were insured, and studies based on primary care systems in high-income and central European countries with universal insurance; or (4) had not measured blood pressure. A list of data sources and their characteristics is provided in the appendix (pp .…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension is an important risk factor for cardiovascular diseases and a serious global problem. The prevalence of hypertension has doubled in the past three decades, accounting for 8.5 million deaths annually worldwide ( 26 , 27 ). More importantly, Hypertension was the most common comorbidity among patients with cancer in a large observational cohort study, with a reported prevalence of 38% ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hypertension was 31.1% in 2010, 28.5% in high-income countries, and 31.5% in low-and middle-income countries (3). An estimated 8.5 million deaths in 2015 were due to systolic blood pressure (SBP) >115 mm Hg, 88% of these deaths were in low-and middle-income countries (4). Worse still, the prevalence of hypertension in low-and middle-income countries is still on the rise (5).…”
Section: Introductionmentioning
confidence: 99%